The bacterial load in milk is associated with clinical severity in cases of bovine coliform mastitis - NAGASAWA, Yuya; KIKU, Yoshio; SUGAWARA, Kazue; YABUSAKI, Takahiro; OONO, Kazuyoshi; FUJII, Kento; SUZUKI, Takahide; MAEHANA, Koji; HAYASHI, Tomohito (Journal of Veterinary Medical Science, 2019)
We evaluated the relationship between the severity of coliform mastitis and bacterial load in 106 quarter milk samples. We found no significant relationship between somatic cell count and coliform bacterial load in milk in bovine clinical coliform mastitis. Results of the Cochran-Armitage test for trend in milk bacterial load proportions indicated a significant decreasing low group (P<0.001), increasing medium group (P<0.002) and increasing high group (P<0.02) with increasing clinical grade. The present study indicates that the coliform bacterial load in milk is significantly associated with clinical severity states in cases of bovine coliform mastitis, and can be a useful indicator for optimal management of this disease.